(untitled) (International Journal of Innovative Research in Engineering & Management, 2023)
Numerous researchers are doing experimental experiments with the goal of identifying potential eco-friendly, cost-efficient, and efficient cement substitute materials. The alternatives include recycling, reusing, and renewing techniques for industrial & agricultural debris, whereby the advantages might be acknowledged. By using these wastes as additional and substitute resources, you may save a lot of energy and use less cement, which both assist to reduce the amount of carbon dioxide released into the environment.Any construction sector needs cement, sand, and aggregate at a minimum. Sand, a material used in the creation of concrete and mortar, is crucial in the blend’s design. Due to river erosion and environmental issues, river sand is currently in limited supply. The structural sector would be affected by the shortage or absence of sand, thus the most cutting-edge alternative material must be explored for replacing river sand so as to prevent excessive river erosion & environmental harm.Mersey silt is among the most significant components that many scientists take into account while discussing other sand-related materials. Various ratios of this silt combined with sand may be used to create the necessary concrete mixture. In order to partially replace natural sand in the manufacturing of concrete, this work examines the different quantities of Mersey silt. This research focuses on the compression & split tensile strength properties of concrete utilising M20 grade concrete combined with Mersey silt as a partial substitute for natural sand (10%, 15%, and 20%).